2017
DOI: 10.3390/coatings7030035
|View full text |Cite
|
Sign up to set email alerts
|

Pitted Corrosion Detection of Thermal Sprayed Metallic Coatings Using Fiber Bragg Grating Sensors

Abstract: Metallic coatings using thermal spraying techniques are widely applied to structural steels to protect infrastructure against corrosion and improve durability of the associated structures for longer service life. The thermal sprayed metallic coatings consisting of various metals, although have higher corrosion resistance, will still corrode in a long run and may also subject to corrosion induced damages such as cracks. Corrosion and the induced damages on the metallic coatings will reduce the effectiveness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…In Figure 14, it was observed that there were multiple spikes on curve of Sample #A1 at range from 95 h to 200 h (4 days to 8 days), indicating the coating structure had been severely corroded. From Figure 14 and the previous study [48], it can be seen that the corrosion progress of the wire-arc Al-Zn coating can be divided into three different phases: Phase 0 (P0 in Figure 14) is the corrosion initialization phase when corrosion products start to fill the pores between adhesive and FBG sensor; Phase 1 (P1 in Figure 14) is the high corrosion rate phase, at which the slope of wavelength change curve in Phase 1 reflects the production rate of corrosion products; and Phase 2 (P2 in Figure 14) is the stabilized corrosion progress, when oxygen further diffuses through the corrosion products and strain caused by corrosion products slowly evanesce, and the remaining sensor reading on the wavelength change curve is primarily remnant stress. Thus, all the experiments stopped after the coating corrosion stayed in Phase 2 for 168 h (7 days).…”
Section: Parameters Valuementioning
confidence: 53%
See 4 more Smart Citations
“…In Figure 14, it was observed that there were multiple spikes on curve of Sample #A1 at range from 95 h to 200 h (4 days to 8 days), indicating the coating structure had been severely corroded. From Figure 14 and the previous study [48], it can be seen that the corrosion progress of the wire-arc Al-Zn coating can be divided into three different phases: Phase 0 (P0 in Figure 14) is the corrosion initialization phase when corrosion products start to fill the pores between adhesive and FBG sensor; Phase 1 (P1 in Figure 14) is the high corrosion rate phase, at which the slope of wavelength change curve in Phase 1 reflects the production rate of corrosion products; and Phase 2 (P2 in Figure 14) is the stabilized corrosion progress, when oxygen further diffuses through the corrosion products and strain caused by corrosion products slowly evanesce, and the remaining sensor reading on the wavelength change curve is primarily remnant stress. Thus, all the experiments stopped after the coating corrosion stayed in Phase 2 for 168 h (7 days).…”
Section: Parameters Valuementioning
confidence: 53%
“…This will result in a shift in Bragg wavelength. The amount of Bragg wavelength change with strains or temperatures can be calculated as below [48]:…”
Section: Operational Principlesmentioning
confidence: 99%
See 3 more Smart Citations